Double-layer membrane framework-based gold microelectrode for determination of natural labile copper in complex water environments - Xinyue Hu; Haitao Han; Shanshan Wang; Dawei Pan (Ecotoxicology and Environmental Safety)
Copper (Cu) is an essential trace element for plankton, but excessive amounts can be toxic and threaten the ecosystems and human health. However, the determination of low concentration labile Cu (CuLabile) in complex water environments remains a huge challenge. In this work, a gold microelectrode (μ-GE) with high sensitivity and anti-fouling capability was fabricated based on a double-layer membrane framework consisting of ion-exchange polymer (Nafion) and agarose gel (LGL). The Nafion stabilized on the surface of μ-GE not only enhanced the voltammetric response significantly through its specific cation-exchange ability with Cu2+, but also improved the chemical and mechanical stability. In addition, the LGL formed an another efficient anti-fouling membrane which could prevent the contamination of electrode by microorganisms, particulate matters, etc. Benefiting from the synergistic effects of the double-layer membrane framework, the so-designed LGL/Nafion functionalized μ-GE (LGL/Nafion/μ-GE) exhibited excellent detection performance for Cu, as well as anti-biofouling capability. Two linear ranges (0.5–10 nM and 10–1000 nM) were achieved for Cu2+, with a detection limit of 0.043 nM in NaCl solution with a salinity of 30 ‰. The LGL/Nafion/μ-GE was successfully applied for the determination of CuLabile in complex environmental water samples including natural seawater and artificial algae culture medium. Furthermore, the real-time changes of CuLabile in culture medium of Synechococcus sp.PCC 7002 was obtained successfully with the LGL/Nafion/μ-GE via in situ continuous monitoring.